Plant growth promoting rhizobacteria increase the efficiency of fertilisers while reducing nitrogen loss. (1st March 2019) - Paungfoo-Lonhienne, Chanyarat; Redding, Matthew; Pratt, Chris; Wang, Weijin
Abstract: More than half of the applied conventional fertiliser nitrogen (N) in cropping systems can be lost to the environment, resulting in water and air pollution. Farming systems that ensure efficient fertiliser use are crucial to sustain crop productivity without harming the environment. One avenue to achieve this is the use of bio-fertilisers with recognised benefits for plant nutrition and soil heath. Within this area, plant growth promoting rhizobacteria (PGPR) are increasingly applied to enhance plant nutrient acquisition and assimilation. Here, we investigated if PGPR can improve fertiliser performance. We show that the addition of PGPR to soils amended with 50% organic and 50% conventional N fertilisers increased the growth of kikuyu grass ( Pennisetum clandestinum ), producing yields similar to those obtained using 100% conventional N fertiliser. Encouragingly, this combination also reduced mineral N leaching by 95% relative to the all conventional fertiliser treatment. These findings suggest that using organic and synthetic fertilisers together in the presence of PGPR is a promising approach for sustaining plant growth while reducing potential pollution from inefficient use of conventional N fertilisers. Graphical abstract: Image 1 Highlights: The PGPR tested had little effects when applied with organic fertiliser alone. PGPR improved plant growth and N uptake when applied together with inorganic and organic fertilisers. Combined use of fertilisers and PGPR decreased N loss from fertilisers.